Energy circulation system based on hydrochloric acid electrolysis

Through an electrolytic energy circulation system based on hydrochloric acid, chlorine and hydrogen hydrochloride reactions are used to generate chlorine and hydrogen hydrochloride reactions to solve the problem of intermediate and instability of new energy power generation technology, and achieve efficient energy storage and release.

CN222411864UActive Publication Date: 2025-01-28QINGDAO BOLIU INNOVATION TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202420979234.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-05-08
Publication Date
2025-01-28
Estimated Expiration
2034-05-08

Smart Images

  • Figure CN222411864U_ABST
    Figure CN222411864U_ABST
Patent Text Reader

Abstract

The utility model belongs to the technical field of electrochemical energy storage, and particularly relates to an efficient energy circulation system based on hydrochloric acid electrolysis. And in the energy storage stage, hydrogen and chlorine evolution reactions are respectively carried out on two poles of the hydrochloric acid electrolysis hydrogen and chlorine evolution system. Chlorine generated by the anode of the hydrochloric acid electrolysis hydrogen and chlorine evolution system is introduced into the chlorine storage device, and hydrogen generated by the cathode of the system is introduced into the hydrogen storage device. Meanwhile, the chlorine storage device is communicated with the cathode of the hydrogen-chlorine fuel cell; and the hydrogen storage device is communicated with the anode of the hydrogen-chlorine fuel cell. In the energy release stage, hydrogen and chlorine react to generate hydrogen chloride, and energy is released. The overpotential in the process is small, so that the energy storage and release efficiency is high, and efficient circulation of the system and efficient storage of energy can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of electrochemical energy storage, and in particular relates to an energy circulation system based on hydrochloric acid electrolysis. Background Art

[0002] The use of new energy for power generation and scientific energy storage is of great significance to the realization of the "dual carbon" goals. Through technological innovation, new energy power generation such as photovoltaic power generation, wind power generation and hydropower generation has made important progress, but there are still shortcomings such as intermittent, instability and dependence on the environment. Although these new energy sources can generate electricity, the above shortcomings make it difficult to integrate the electricity they generate into the existing power system. Realizing large-scale and efficient energy storage is very important for achieving efficient utilization of volatile renewable energy.

[0003] Using electrolysis of water to produce green hydrogen and then using fuel cells to release electricity when energy is needed is an effective method for large-scale, cross-seasonal utilization of renewable energy, but the overall energy utilization efficiency is not high.

[0004] In order to solve the above problems, this application is proposed. Utility Model Content

[0005] In the process of realizing the present invention, the applicant found that the main reason for the low energy efficiency of the above process is that the overpotential of oxygen evolution in the oxygen part is large, often exceeding 200mV; the overpotential of oxygen reduction reaction is also over 0.3V. However, the applicant found through research that the overpotential of chlorine evolution and chlorine reduction reaction is much smaller, and thus becomes a better alternative reaction, and therefore proposed the present invention.

[0006] The purpose of the utility model is to provide an energy circulation system based on hydrochloric acid electrolysis, using a high-performance catalyst to achieve good energy circulation, and to solve the problem of new energy power storage to the greatest extent.

[0007] The chlorine evolution reaction is the anode reaction in the hydrochloric acid electrolysis system for hydrogen evolution and chlorine evolution. At the same time, as a high-energy-consuming anode reaction in the traditional chlor-alkali industry, its reaction overpotential is small, and the reverse reaction overpotential is also small. The inventive point of the present application is to find that the chlorine evolution reaction can be matched with the hydrogen redox reaction to form a more efficient energy circulation storage system.

[0008] In the process of using new energy to generate electricity, the excess electricity that is not transported by the power grid is efficiently electrolyzed into hydrochloric acid solution to obtain chlorine and hydrogen, converting intermittent electricity into chemical energy for storage. When the power grid needs electricity, the chlorine and hydrogen produced in the above process are used as fuel to the hydrogen-chlorine fuel cell, which uses high-performance catalysts to achieve high-performance discharge while producing hydrochloric acid, realizing the circulation of energy.

[0009] The present application provides an energy circulation system based on hydrochloric acid electrolysis, the energy circulation system comprising: a hydrochloric acid storage device 1, a hydrochloric acid electrolysis hydrogen and chlorine evolution system 2, a hydrogen storage device 5, a chlorine storage device 6, and a hydrogen-chlorine fuel cell 7;

[0010] Wherein, the hydrochloric acid storage device 1 is connected to the anode of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system 2 through the material hydrochloric acid input pipeline 101, or the hydrochloric acid storage device 1 is respectively connected to the anode and cathode of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system 2 through the material hydrochloric acid input pipeline 101, the anode of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system 2 is connected to the chlorine storage device 6, and the chlorine storage device 6 is connected to the cathode of the hydrogen-chlorine fuel cell 7 through the chlorine input pipeline 109;

[0011] The cathode of the hydrochloric acid electrolysis hydrogen and chlorine evolution system 2 is connected to the hydrogen storage device 5, and the hydrogen storage device 5 is connected to the anode of the hydrogen-chlorine fuel cell 7 through the hydrogen input pipeline 108;

[0012] The cathode of the hydrogen-chlorine fuel cell 7 is also connected to the hydrochloric acid storage device 1 .

[0013] When the hydrochloric acid storage device 1 is connected only to the anode of the hydrochloric acid electrolysis and hydrogen evolution and chlorine evolution system 2 through the hydrochloric acid material input pipeline 101, the protons in the electrolyte can penetrate into the cathode side of the hydrochloric acid electrolysis and hydrogen evolution and chlorine evolution system 2 through the proton exchange membrane, and finally hydrogen is obtained at the cathode.

[0014] Preferably, the energy circulation system further comprises a chlorine separation device 4;

[0015] The anode of the hydrochloric acid electrolysis hydrogen evolution and chlorine evolution system 2 is connected to the chlorine separation device 4 through a chlorine / hydrochloric acid output pipeline 102, and the chlorine separation device 4 is connected to the chlorine storage device 6 through a chlorine output pipeline 105.

[0016] Preferably, a chlorine compression device is provided in the chlorine storage device 6, or a chlorine compression device is provided between the chlorine output pipeline 105 and the chlorine storage device 6, so as to pressurize and liquefy the chlorine.

[0017] Preferably, the lower part of the chlorine separation device 4 is connected to the hydrochloric acid storage device 1 through a second hydrochloric acid reflux pipeline 107 .

[0018] Preferably, the energy circulation system further comprises a hydrogen separation device 3;

[0019] The cathode of the hydrochloric acid electrolysis hydrogen and chlorine evolution system 2 is connected to the hydrogen separation device 3 through a hydrogen / hydrochloric acid output pipeline 103, and the hydrogen separation device 3 is connected to the hydrogen storage device 5 through a hydrogen output pipeline 104.

[0020] Preferably, the lower part of the hydrogen separation device 3 is connected to the hydrochloric acid storage device 1 through a first hydrochloric acid reflux pipeline 106 .

[0021] Preferably, the energy circulation system further comprises a chlorine / hydrogen chloride separation device 8;

[0022] The cathode of the hydrogen-chlorine fuel cell 7 is connected to the chlorine / hydrogen chloride separation device 8 through a chlorine / hydrogen chloride output pipeline 111, the upper part of the chlorine / hydrogen chloride separation device 8 is connected to the chlorine storage device 6 through a chlorine reflux pipeline 112, and the lower part of the chlorine / hydrogen chloride separation device 8 is connected to the hydrochloric acid storage device 1.

[0023] Preferably, the energy circulation system further comprises a hydrochloric acid recovery and purification device 9;

[0024] The lower part of the chlorine / hydrogen chloride separation device 8 is connected to the hydrochloric acid recovery and purification device 9 through a hydrochloric acid / saturated brine transport pipeline 113, one outlet of the hydrochloric acid recovery and purification device 9 is connected to the hydrochloric acid storage device 1 through a hydrogen chloride reflux pipeline 115, and the other outlet of the hydrochloric acid recovery and purification device 9 is connected to the chlorine / hydrogen chloride separation device 8 through a saturated brine reflux pipeline 114.

[0025] Preferably, the anode of the hydrogen-chlorine fuel cell 7 is also connected to the hydrogen storage device 5 via a hydrogen reflux pipeline 110 .

[0026] Optional designs for the above pipelines include pumps, valves and flow meters.

[0027] The electrolytic hydrochloric acid hydrogen and chlorine evolution system 2 also includes a corrosion-resistant liquid pump, a power supply access system, and a tail gas drying and dehydration device.

[0028] The second aspect of the present application provides a working method of the energy circulation system based on hydrochloric acid electrolysis according to the first aspect, and the working method comprises:

[0029] The hydrochloric acid electrolysis hydrogen evolution and chlorine evolution system 2 is connected by electric energy, and the hydrochloric acid provided in the hydrochloric acid storage device 1 is used as the electrolyte, and a chlorine evolution reaction and a hydrogen evolution reaction occur to obtain chlorine and hydrogen. The chlorine output in this process is sent to the chlorine storage device 6 for storage and standby use, and the hydrogen output in this process is sent to the hydrogen storage device 5 for storage and standby use;

[0030] The chlorine storage device 6 and the hydrogen storage device 5 are respectively input into the cathode and anode of the hydrogen-chlorine fuel cell 7. The chlorine and hydrogen react in the hydrogen-chlorine fuel cell 7 to obtain hydrogen chloride and generate electrical energy. The hydrogen chloride flows back to the hydrochloric acid storage device 1 for recycling.

[0031] Preferably, the chlorine is pressurized and liquefied in the chlorine storage device 6, or the chlorine is pressurized and liquefied before being sent to the chlorine storage device 6. Preferably, the pressure of the pressurized liquefaction is equal to or greater than 2 MPa.

[0032] Preferably, the anode in the hydrochloric acid electrolysis hydrogen and chlorine evolution system 2 is a mixed metal oxide electrode.

[0033] The mixed metal oxide electrode comprises a conductive substrate and a mixed metal oxide supported on the conductive substrate, wherein the molecular formula of the mixed metal oxide is M x Ru 1-x O2;

[0034] Wherein, M is two or more of Ti, Sn, Sb, Nb, Zr, V, Co, Fe, and Ni;

[0035] x is the mole fraction of all metals in M ​​and M x Ru 1-x The molar fraction ratio of all metals in O2, x = 20 ~ 70%.

[0036] The above-mentioned multiple types refer to more than two types, for example, three, four, five, six, seven, eight, or nine types.

[0037] Preferably, the mixed metal oxide electrode has a mud-cracked surface, and the mud-cracked surface is composed of nanoparticles with a size of 5 to 100 nanometers.

[0038] Preferably, the metal elements in the mixed metal oxide are uniformly dispersed.

[0039] Preferably, the conductive substrate is a porous carbon material or a porous metal material.

[0040] The preparation method of the mixed metal oxide electrode comprises the following steps:

[0041] (1) preparing alcohol solutions of different metals respectively;

[0042] The alcohol solution of different metals is a middle metal including ruthenium and M;

[0043] Wherein, M is two or more of Ti, Sn, Sb, Nb, Zr, V, Co, Fe, and Ni;

[0044] (2) mixing the alcohol solutions of different metals prepared in step (1) to obtain a mixed solution in which the different metals are evenly dispersed, wherein the molar ratio of ruthenium to M in the mixed solution is 1-x:x, wherein x = 20% to 70%;

[0045] Then, a high molecular weight polymer having a multidentate ligand is added to the mixed solution, and the mixture is heated and stirred to fully react with the solution to be coated;

[0046] (3) brushing the solution to be coated obtained in step (2) onto the conductive substrate, heating and drying, and performing the coating-heating and drying process 1 to 4 times in total;

[0047] (4) calcining the coated conductive substrate in air and then cooling it to room temperature in air, and the calcination-cooling process is performed 1 to 4 times in total;

[0048] (5) The coated conductive substrate is then calcined in air and cooled to room temperature in a furnace to obtain a mixed metal oxide electrode.

[0049] Preferably, the high molecular weight polymer having a multidentate ligand added in step (2) is selected from one or more of polyvinyl alcohol, polyethylene glycol, polyethylenediamine and polyvinylpyrrolidone.

[0050] Preferably, in the step (2), in the solution to be coated, the ratio of the high molecular weight polymer having multidentate ligands to the total metal is (60-240 mg): (0.5-2 mmol).

[0051] Preferably, in step (2), the heating and stirring is performed at a temperature of 50-90° C. and for a time of 2-8 h;

[0052] The drying temperature in step (3) is 50-90° C., and the drying time is 1-20 min.

[0053] In the step (4), the calcination temperature is 400-600° C., and the calcination time is 1-20 min.

[0054] The calcination temperature in step (5) is 400-600° C., and the calcination time is 0.5-3 h.

[0055] Preferably, the conductive substrate is a porous conductive substrate, and specifically, a porous carbon material or a porous metal material can be selected. The porous metal material can be titanium felt, titanium mesh, etc. The porous carbon material can be carbon paper, carbon cloth, etc.

[0056] Preferably, the hydrochloric acid electrolysis hydrogen and chlorine evolution system 2 further comprises: titanium-based anode and cathode plates, and proton exchange membrane electrodes. The proton exchange membrane electrodes comprise a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer on both sides of the proton exchange membrane.

[0057] The titanium-based anode and cathode plates are corrosion-resistant and thus can withstand corrosion from electrolyte during use.

[0058] The proton exchange membrane can be selected from Nafion perfluorosulfonic acid membrane, Hancheng Hyproof enhanced perfluorosulfonic acid proton exchange membrane, and fumapem perfluorosulfonic acid / polytetrafluoroethylene copolymer membrane.

[0059] The cathode catalyst is selected from noble metal catalysts, such as carbon-supported platinum, ruthenium, iridium, palladium and other metals.

[0060] The electrolyte in the hydrochloric acid electrolysis hydrogen evolution chlorine evolution system 2 is 0.1-10 mol L -1 Concentration of hydrochloric acid, the catalyst loading on the electrode is: 2-10 mg cm -2 .

[0061] Preferably, the hydrogen-chlorine fuel cell 7 comprises: titanium-based anode and cathode plates, and a proton exchange membrane electrode.

[0062] The proton exchange membrane may be, for example, Nafion perfluorosulfonic acid membrane, Hancheng Hyproof enhanced perfluorosulfonic acid proton exchange membrane, or fumapem perfluorosulfonic acid / polytetrafluoroethylene copolymer membrane.

[0063] The anode catalyst can be selected from existing precious metal catalysts such as carbon-supported platinum, ruthenium, iridium, palladium and other metals.

[0064] The cathode catalyst can be selected from existing precious metal catalysts such as carbon-supported platinum, ruthenium, iridium, palladium and other metals.

[0065] Preferably, the catalyst loading is 2 to 10 mg cm -2 .

[0066] According to the Hume-Rothery rule, when the difference in the size of the constituent atoms is less than 14-15%, it is conducive to the formation of a solid solution with a larger solid solubility (solubility limit); when it is greater than 15%, it is not conducive to the formation of a solid solution. Regulating the electronic structure of the electrocatalyst by doping other elements with appropriate size and electronegativity is one of the commonly used and effective ways to improve the electrocatalytic performance. Therefore, the present application develops an efficient and low-cost electrocatalytic chloride ion oxidation catalyst by doping and modifying ruthenium dioxide with relatively low-cost non-precious metal oxides.

[0067] The mixed metal oxide electrode is prepared by a sol-gel method. The electrode belongs to a low-noble metal mixed oxide electrode. In the electrode, the noble metal iridium is not used, and the amount of relatively cheap noble metal ruthenium is reduced. While greatly reducing the preparation cost of the DSA electrode, the electrochemical activity and chlorine oxidation selectivity are better than those of commercial DSA, and it shows good stability. The electrode preparation method is simple and can be mass-produced and applied.

[0068] The applicant discovered during the implementation of this application that:

[0069] Four-electron transfer O2 / O in common hydrogen-oxygen fuel cells 2- The reaction overpotential is generally above 150mV. This part of the potential is completely consumed in order to promote the reaction and cannot be used.

[0070] Compared with O2 / O 2- Reaction, in hydrogen-chlorine fuel cells, Cl2 / Cl - The overpotential of the reaction is only 0-20mV, Cl2 / Cl - The redox pair has fast kinetics and excellent redox reversibility. - The theoretical potential of the redox couple is as high as 1.36 V vs. SHE, and the energy storage capacity can reach 755 mAh g -1 , is the vanadium oxide (VO2 + / VO 2+ , more than twice that of 226mAh / g).

[0071] Therefore, the hydrogen-chlorine fuel cell of the present application has less energy loss than the hydrogen-oxygen fuel cell.

[0072] Compared with the prior art, this application has the following beneficial effects:

[0073] 1. The energy circulation system based on hydrochloric acid electrolysis of the present application relates to the hydrochloric acid electrolysis hydrogen evolution chlorine evolution reaction, and hydrogen-chlorine fuel cell technology. For the first time, the hydrochloric acid electrolysis hydrogen evolution chlorine evolution system and the hydrogen-chlorine fuel cell are combined, and electric energy is used to efficiently electrolyze hydrochloric acid to obtain chlorine and hydrogen respectively, and the electric energy is converted into chemical energy for storage. When electric energy is needed, the chlorine and hydrogen generated by the above process are used as fuel to pass to the hydrogen-chlorine fuel cell, and hydrochloric acid is obtained by reaction, thereby realizing the conversion of chemical energy into electric energy. The hydrochloric acid obtained by the reaction can be recycled as a raw material for the hydrochloric acid electrolysis hydrogen evolution chlorine evolution system. Since the overpotential of the above process is small, the overpotential of chlorine evolution and hydrogen evolution can be as low as 0-20mV, so the energy storage and release efficiency is high, and the efficient circulation of the system can be realized.

[0074] 2. In the energy circulation system of the present application, chlorine is easy to liquefy and store, and the hydrogen storage method is mature. Therefore, the system of the present application has the advantages of high energy storage density, convenient transportation of compressed gas energy storage, and high material and energy circulation efficiency.

[0075] 3. In particular, the present application also discloses a high-performance mixed metal oxide electrode. The inventors have found that in this electrode, doping metal elements in ruthenium dioxide has significant advantages: (1) In terms of activity, the appropriate doping of metals such as Ti, Sn, Sb, Nb, Zr, V, Co, Fe, and Ni can adjust the electronic structure of the oxygen active site, which is beneficial to its adsorption of chlorine, thereby reducing the free energy of the rate-determining step and improving the catalytic activity of the electrode. However, too much or too little element doping cannot achieve the desired effect: if the element doping is small (i.e., x<20%), the change in the performance of the ruthenium dioxide electrode is not obvious, and its preparation cost is not significantly reduced, and the actual application value is not great; if the element doping is large (i.e., x>70%), the crystal structure of ruthenium dioxide is prone to large distortion, the electrode material will undergo phase separation, and impurity phases will be generated, causing the performance to decay rapidly.

[0076] (2) In terms of stability, the main reason why traditional ruthenium dioxide-based catalysts are not stable under long-term oxidation conditions is that ruthenium dioxide is easily over-oxidized to soluble species and dissolved in the electrolyte at an oxidation potential. However, when non-precious metals are doped into ruthenium dioxide nanomaterials, the covalency of the Ru-O bond is weakened due to the introduction of doped metals, so that ruthenium is in a lower valence state, which inhibits its over-oxidation at the oxidation potential during the reaction process, so that the electrode material shows good stability in the electrocatalytic chloride ion oxidation reaction. During the stability test, under the working conditions of high current density, the constant current polarization curve can still remain stable for a long time. Moreover, during the preparation process, the doped metals such as Ti, Sn, and Sb all use their highest valence compounds as transition metal sources. The high temperature and high pressure liquid environment can make them fully oxidized, and their oxides have strong stability, so they can stably play a role in regulating ruthenium sites in the electrolyte, so that the stability of the electrode is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0077] Figure 1 The Zr obtained in Examples 1, 3, 5, and 7 respectively 0.6 Sb 0.1 Ru 0.3 O2 electrode, Zr 0.6 V 0.1 Ru 0.3 O2 electrode, Sn 0.6 Nb 0.1 Ru 0.3 O2 electrode, Sn 0.6 Ti 0.1 Ru 0.3 SEM image of O2 electrode.

[0078] Figure 2 It is Zr 0.6 Sb 0.1 Ru0.3 Surface element distribution map of O2 electrode.

[0079] Figure 3 It is Zr 0.6 V 0.1 Ru 0.3 Surface element distribution map of O2 electrode.

[0080] Figure 4 It's Sn 0.6 Nb 0.1 Ru 0.3 Surface element distribution map of O2 electrode.

[0081] Figure 5 It's Sn 0.6 Ti 0.1 Ru 0.3 Surface element distribution map of O2 electrode.

[0082] Figure 6 It is Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 TEM image of particles on the surface of O2 electrode.

[0083] Figure 7 The nine curves A, B, C, D, E, F, G, H, and I are respectively the Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru0.7 O2 electrode, Ti 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.0 7Ni 0.07 Ru 0.3 Polarization curves of electrocatalytic chlorine production under acidic conditions on O2 electrode and commercial ruthenium-iridium DSA electrode.

[0084] Figure 8 The nine curves A, B, C, D, E, F, G, H, and I are respectively the Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2 electrode, Ti 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.0 7Ni 0.07 Ru 0.3 Chlorine selectivity bar graph of O2 electrode and commercial Ru-Ir DSA electrode.

[0085] Fig. 9 The five curves A, B, C, D, and E are the Zr 0.6 Sb 0.1 Ru 0.3 O2 electrode, Zr 0.1 Sb 0.1 Ru 0.8 O2 electrode, Zr 0.7Sb 0.1 Ru 0.2 O2 electrode, Zr 0.05 Sb 0.05 Ru 0.9 Polarization curves of electrocatalytic chlorine production on O2 electrode and commercial Ru-Ir DSA electrode.

[0086] Fig.10 The five curves A, B, C, D, and E are the Zr 0.6 V 0.1 Ru 0.3 O2 electrode, Zr 0.1 V 0.1 Ru 0.8 O2 electrode, Zr 0.7 V 0.1 Ru 0.2 O2 electrode, Zr 0.05 V 0.05 Ru 0.9 Polarization curves of electrocatalytic chlorine production on O2 electrode and commercial Ru-Ir DSA electrode.

[0087] Fig.11 The five curves A, B, C, D, and E are respectively the Sn 0.6 Nb 0.1 Ru 0.3 O2 electrode, Sn 0.1 Nb 0.1 Ru 0.8 O2 electrode, Sn 0.7 Nb 0.1 Ru 0.2 O2 electrode, Sn 0.05 Nb 0.05 Ru 0.9 Polarization curves of electrocatalytic chlorine production on O2 electrode and commercial Ru-Ir DSA electrode.

[0088] Fig.12 The five curves A, B, C, D, and E are respectively the Sn 0.6 Ti 0.1 Ru 0.3 O2 electrode, Sn 0.1 Ti 0.1 Ru 0.8 O2 electrode, Sn 0.7 Ti 0.1 Ru 0.2 O2 electrode, Sn 0.05 Ti 0.05 Ru 0.9 Polarization curves of electrocatalytic chlorine production on O2 electrode and commercial Ru-Ir DSA electrode.

[0089] Fig.13The five curves A, B, C, D, and E are the Zr 0.6 Sb 0.1 Ru 0.3 O2 electrode, Zr 0.6 V 0.1 Ru 0.3 O2 electrode, Sn 0.6 Nb 0.1 Ru 0.3 O2 electrode, Sn 0.6 Ti 0.1 Ru 0.3 Stability test curves of electrocatalytic chlorine production of O2 electrode and commercial ruthenium-iridium DSA electrode.

[0090] Fig.14 The nine curves A, B, C, D, E, F, G, H, and I are Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2 electrode, Ti 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.07 Ni 0.07 Ru 0.3 Polarization curves of electrocatalytic production of hypochlorous acid under neutral conditions on O2 electrode and commercial Ru-Ir DSA electrode.

[0091] Fig.15 The nine curves A, B, C, D, E, F, G, H, and I are Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2 electrode, Ti 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.07 Ni 0.07 Ru 0.3 Polarization curves of electrocatalytic hypochlorite production under alkaline conditions on O2 electrode and commercial Ru-Ir DSA electrode.

[0092] Fig.16 This is a schematic diagram of the energy circulation system structure based on hydrochloric acid electrolysis.

[0093] Fig.17 This is a schematic diagram of the energy circulation system based on hydrochloric acid electrolysis.

[0094] Fig.18 In the figure, a is the electrocatalytic chlorine reduction polarization curve of carbon nanotube-supported Pt clusters, RuO2 electrode and commercial ruthenium-iridium DSA electrode, and b is the electrocatalytic hydrogen oxidation polarization curve of carbon-supported platinum, carbon-supported iridium and carbon-supported ruthenium.

[0095] Description of reference numerals:

[0096] 1-Hydrochloric acid storage device; 2-Electrolytic hydrochloric acid hydrogen and chlorine evolution system; 3-Hydrogen separation device; 4-Chlorine separation device; 5-Hydrogen storage device; 6-Chlorine storage device; 7-Hydrogen-chlorine fuel cell; 8-Chlorine / hydrogen chloride separation device; 9-Hydrochloric acid recovery and purification device.

[0097] 101-Material hydrochloric acid input pipeline; 102-Chlorine / hydrochloric acid output pipeline; 103-Hydrogen / hydrochloric acid output pipeline; 104-Hydrogen output pipeline; 105-Chlorine output pipeline; 106-Hydrochloric acid reflux pipeline; 107-Hydrochloric acid reflux pipeline; 108-Hydrogen input pipeline; 109-Chlorine input pipeline; 110-Hydrogen reflux pipeline; 111-Chlorine / hydrogen chloride output pipeline; 112-Chlorine reflux pipeline; 113-Hydrochloric acid / saturated brine transport pipeline; 114-Saturated brine reflux pipeline; 115-Hydrogen chloride reflux pipeline. DETAILED DESCRIPTION

[0098] The present application is further described in detail below in conjunction with embodiments.

[0099] Those skilled in the art will appreciate that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or the product specifications are used. If the manufacturer of the materials or equipment used is not specified, they are all conventional products that can be purchased.

[0100] Those skilled in the art will appreciate that, unless expressly stated otherwise, the singular forms "a", "an", "said" and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present application refers to the presence of the features, integers, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or groups thereof. It should be understood that when we refer to an element as being "connected" to another element, it may be directly connected to the other element, or there may be intermediate elements. In addition, the "connection" used herein may include wireless connections.

[0101] In the description of this application, unless otherwise specified, "plurality" means two or more. The terms "inside", "upper", "lower", etc. indicate positions or state relationships based on the positions or state relationships shown in the drawings, which are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific position, be constructed and operate in a specific position, and therefore cannot be understood as limiting this application.

[0102] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "provided with" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in this application are understood according to specific circumstances.

[0103] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein, including technical and scientific terms, have the same meaning as those generally understood by those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in common dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless defined as herein.

[0104] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0105] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If not otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution. If not otherwise specified, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0106] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0107] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B".

[0108] In the present application, the hydrochloric acid storage device in the energy circulation system is connected to the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system and the hydrogen-chlorine fuel cell, and hydrochloric acid serves as both a reactant and an electrolyte. In the energy storage stage, hydrogen evolution and chlorine evolution reactions occur at the two poles of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system. The chlorine produced by the anode of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system is passed to the chlorine storage device, and the hydrogen produced by the cathode is passed to the hydrogen storage device. At the same time, the chlorine storage device is connected to the cathode of the hydrogen-chlorine fuel cell; the hydrogen storage device is connected to the anode of the hydrogen-chlorine fuel cell. In the energy release stage, hydrogen and chlorine react in the hydrogen-chlorine fuel cell to generate hydrogen chloride and release energy. When the electric energy is abundant, the present application uses electric energy to efficiently electrolyze hydrochloric acid to obtain chlorine and hydrogen respectively, and converts the electric energy into chemical energy for storage. When electric energy is needed, the chlorine and hydrogen generated by the above process are used as fuel to pass to the hydrogen-chlorine fuel cell to realize the conversion of chemical energy into electric energy. The hydrochloric acid obtained by the reaction can be recycled as a raw material for the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system. Since the overpotential of the above process is small, the energy storage and release efficiency is high, which can achieve efficient circulation of the system and efficient storage of energy.

[0109] The carbon nanotube-supported Pt clusters, RuO2 electrodes, and commercial ruthenium-iridium DSA electrodes used in this application are sourced from Sigma-Aldrich.

[0110] Fig.16 This is an energy circulation system based on hydrochloric acid electrolysis in this embodiment. The energy circulation system includes: a hydrochloric acid storage device 1, a hydrochloric acid electrolysis hydrogen and chlorine evolution system 2, a hydrogen separation device 3, a chlorine separation device 4, a hydrogen storage device 5, a chlorine storage device 6, and a hydrogen-chlorine fuel cell 7;

[0111] The hydrochloric acid storage device 1 is connected to the cathode and anode of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system 2 through a material hydrochloric acid input pipeline 101 to supply hydrochloric acid as an electrolyte. The anode of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system 2 is connected to a chlorine storage device 6 to liquefy and store the chlorine generated by electrolysis, and the chlorine storage device 6 is connected to the cathode of the hydrogen-chlorine fuel cell 7 through a chlorine input pipeline 109 to supply chlorine to the hydrogen-chlorine fuel cell 7.

[0112] The cathode of the hydrochloric acid electrolysis hydrogen and chlorine evolution system 2 is connected to the hydrogen storage device 5 to store the hydrogen generated by electrolysis, and the hydrogen storage device 5 is connected to the anode of the hydrogen-chlorine fuel cell 7 through a hydrogen input pipeline 108 to supply hydrogen to the hydrogen-chlorine fuel cell 7.

[0113] The cathode of the hydrogen-chlorine fuel cell 7 is also connected to the hydrochloric acid storage device 1 to recover the hydrochloric acid produced by the battery reaction.

[0114] In this embodiment, the energy circulation system further includes a chlorine separation device 4;

[0115] The anode of the hydrochloric acid electrolysis hydrogen evolution and chlorine evolution system 2 is connected to the chlorine separation device 4 through a chlorine / hydrochloric acid output pipeline 102, and the chlorine separation device 4 is connected to the chlorine storage device 6 through a chlorine output pipeline 105.

[0116] In this embodiment, the lower part of the chlorine separation device 4 is connected to the hydrochloric acid storage device 1 through the second hydrochloric acid reflux pipeline 107, so that the separated liquid hydrochloric acid refluxes to the hydrochloric acid storage device 1.

[0117] In this embodiment, the energy circulation system further includes a hydrogen separation device 3;

[0118] The cathode of the hydrochloric acid electrolysis hydrogen and chlorine evolution system 2 is connected to the hydrogen separation device 3 through a hydrogen / hydrochloric acid output pipeline 103, and the hydrogen separation device 3 is connected to the hydrogen storage device 5 through a hydrogen output pipeline 104.

[0119] In this embodiment, the lower part of the hydrogen separation device 3 is connected to the hydrochloric acid storage device 1 through the first hydrochloric acid reflux pipeline 106 so that the separated liquid hydrochloric acid can flow back to the hydrochloric acid storage device 1.

[0120] Of course, it is conceivable that the purpose of the present application can be achieved without designing the chlorine separation device 4 and the hydrogen separation device 3 in certain embodiments.

[0121] In this embodiment, the energy circulation system further includes a chlorine / hydrogen chloride separation device 8;

[0122] The cathode of the hydrogen-chlorine fuel cell 7 is connected to the chlorine / hydrogen chloride separation device 8 through a chlorine / hydrogen chloride output pipeline 111, the upper part of the chlorine / hydrogen chloride separation device 8 is connected to the chlorine storage device 6 through a chlorine reflux pipeline 112, and the lower part of the chlorine / hydrogen chloride separation device 8 is connected to the hydrochloric acid storage device 1.

[0123] In this embodiment, the energy circulation system further includes a hydrochloric acid recovery and purification device 9;

[0124] The lower part of the chlorine / hydrogen chloride separation device 8 is connected to the hydrochloric acid recovery and purification device 9 through a hydrochloric acid / saturated brine transport pipeline 113, one outlet of the hydrochloric acid recovery and purification device 9 is connected to the hydrochloric acid storage device 1 through a hydrogen chloride reflux pipeline 115, and the other outlet of the hydrochloric acid recovery and purification device 9 is connected to the chlorine / hydrogen chloride separation device 8 through a saturated brine reflux pipeline 114.

[0125] Of course, it is conceivable that the purpose of the present application can be achieved without designing the chlorine / hydrogen chloride separation device 8 and the hydrochloric acid recovery and purification device 9 in certain embodiments.

[0126] In this embodiment, a saturated salt water bottle is provided in the chlorine / hydrogen chloride separation device 8 to absorb the hydrogen chloride. The hydrochloric acid recovery and purification device 9 purifies the hydrogen chloride by distillation, and the heating evaporation temperature is 80-85°C.

[0127] The hydrogen separation device 3 and the chlorine separation device 4 can be selected from conventional gas-liquid separation devices.

[0128] In this embodiment 1, the chlorine separation device 4 is connected to the chlorine storage device 6 through the chlorine output pipeline 105, and then passes through a dehydration device to dry the chlorine, and is pressurized to 2 MPa for liquefaction by a chlorine compression device. The chlorine compression device is a chlorine compressor.

[0129] The hydrogen separation device 3 is also passed through a dehydration device to dry the hydrogen before being connected to the hydrogen storage device 5 through the hydrogen output pipeline 104. The dehydration device can be selected to wash the bottle with concentrated sulfuric acid. In this embodiment, the anode of the hydrogen-chlorine fuel cell 7 is also connected to the hydrogen storage device 5 through a hydrogen reflux pipeline 110. The hydrogen tail gas output from the anode of the hydrogen-chlorine fuel cell 7 does not need to remove hydrochloric acid. In the anode hydrogen oxidation process, only protons are transferred to the cathode to contact with the chloride ions obtained by chlorine reduction to form hydrogen chloride, and the hydrogen chloride does not pass through the membrane and mix into the hydrogen tail gas of the anode.

[0130] The hydrogen-chlorine fuel cell comprises a corrosion-resistant gas flow controller, a corrosion-resistant titanium metal electrode plate, a proton exchange membrane electrode, and a chlorine / hydrogen chloride separation device.

[0131] The hydrochloric acid recovery and purification device comprises a pH monitor, a hydrochloric acid condensing device, and a tail gas absorption device.

[0132] The gas storage device in the energy circulation system is used to store the chlorine and hydrogen produced by the electrolysis of hydrochloric acid for standby use. When the hydrogen-chlorine fuel cell 7 needs to discharge, the two are respectively connected to its chlorine fuel inlet and hydrogen fuel inlet to be transported to the cathode and anode of the hydrogen-chlorine fuel cell 7 respectively, and the effect of controllable hydrogen-chlorine fuel cell power generation is achieved through the corrosion-resistant gas flow controller.

[0133] Main operating conditions:

[0134] Operating temperature: 20~40℃

[0135] Hydrochloric acid material flow rate: 90~130L / h

[0136] Hydrochloric acid electrolysis output tail gas flow rate: 30~110mL / min (depending on electrolysis current)

[0137] Hydrogen and chlorine main pipe pressure: 17518.7~63094.4N / m 2 (depending on electrolysis current)

[0138] Hydrochloric acid concentration: 0.1~10mol L -1

[0139] Hydrogen-chlorine fuel cell output current: 20~30A

[0140] Output voltage: 0.6~0.9V

[0141] Output power: 17~20W

[0142] Current density: 0.8~1.2A cm -2

[0143] Energy density: 0.68-0.8W cm -2

[0144] The working process of the energy circulation system based on hydrochloric acid electrolysis is as follows:

[0145] Using intermittent power input, connect to hydrochloric acid electrolysis system 2, with 0.1~10mol L -1 The hydrochloric acid is used as the electrolyte to produce chlorine and hydrogen by chlorine evolution reaction and hydrogen evolution reaction. The operating conditions are normal pressure and the flow rates of the anode and cathode liquids are 90-130 L / h respectively. The specific reactions are:

[0146] Anode: 2Cl - -2e - =Cl2;

[0147] Cathode: 2H + +2e - =H2;

[0148] Overall reaction formula: 2HCl=Cl2+H2;

[0149] The chlorine gas outputted from this process is sent to the chlorine storage device 6 for liquefaction and storage via the chlorine separation device 4, and the liquid hydrochloric acid obtained via the chlorine separation device 4 is refluxed to the hydrochloric acid storage device 1. The hydrogen gas outputted from this process is sent to the hydrogen storage device 5 for storage via the hydrogen separation device 3, and the hydrochloric acid obtained via the hydrogen separation device 3 is refluxed to the hydrochloric acid storage device 1.

[0150] Generally, the anodic oxygen evolution reaction in water electrolysis is a four-electron transfer reaction, which requires an overpotential of at least 150 millivolts to overcome the reaction energy barrier; while the anodic chlorine evolution reaction in hydrochloric acid electrolysis is a two-electron transfer reaction, which only requires an overpotential of 0-20 millivolts to overcome the reaction energy barrier. Therefore, compared with water electrolysis, the hydrochloric acid electrolysis hydrogen evolution system has a higher energy utilization efficiency.

[0151] The hydrogen-chlorine fuel cell is similar to the reverse process of the above process, with operating conditions of normal temperature and pressure, and anode and cathode gas flow rates of 30 to 110 mL / min. Hydrogen and chlorine are derived from the above process and are electrolytically separated and stored in a hydrogen-chlorine storage device, which are connected to the hydrogen inlet and chlorine inlet of the hydrogen-chlorine fuel cell respectively. Specifically, hydrogen is oxidized at the anode of the proton exchange membrane electrode, and the chemical reaction process is H2-2e - =2H + , producing protons and passing through the proton exchange membrane to the cathode of the proton exchange membrane electrode, where they meet the chloride ions obtained by the reaction with chlorine to produce hydrogen chloride. Chlorine is reduced at the cathode of the proton exchange membrane electrode, and the chemical reaction process is Cl2+2e - =2Cl - The overall chemical reaction in the fuel cell is H2+Cl2=2HCl. The cathode tail gas chlorine and the hydrogen chloride obtained by the reaction pass through the chlorine / hydrogen chloride separation device 8. The obtained chlorine is refluxed to the chlorine storage device 6. The obtained hydrogen chloride passes through the hydrochloric acid recovery and purification device 9, and then the purified hydrochloric acid is refluxed to the hydrochloric acid storage device 1, realizing the circulation of materials and energy.

[0152] Fig.17 This is a schematic diagram of the principle of the energy circulation system based on hydrochloric acid electrolysis. The figure shows the high reversibility of the hydrogen evolution reduction reaction and the hydrogen oxidation reaction, as well as the high reversibility of the chlorine evolution oxidation reaction and the chlorine reduction reaction. The combination of the two reflects the complete reversibility of the energy circulation system of hydrochloric acid electrolysis.

[0153] The overall reaction formula of hydrogen-chlorine fuel cell: H2+Cl2=2HCl;

[0154] Average voltage of hydrogen-chlorine fuel cell: Ev = 1.36-0 = 1.36V;

[0155] The energy produced by 1 mol of hydrogen is 1.36V×96485C=131219.6J=36.45Wh, and the energy produced by 1 kg of H2 (1 kg of H2 also consumes 35.5 kg of Cl2) is 1000 / 2×36.45÷1000=18.225 kWh;

[0156] The specific energy is: 18.225 kWh / (1 kg+35.5 kg)=0.5 kWh / kg.

[0157] Therefore, compared with other energy storage methods, this battery has a higher specific energy. The comparison results are shown in Table 1 below.

[0158] Table 1. Comparison of energy storage density (specific energy) of hydrogen-chlorine fuel cells and other existing energy storage methods

[0159]

[0160] The energy storage density data of other existing energy storage methods comes from patent CN 106785242 B.

[0161] In addition, in the hydrogen-oxygen fuel cells that are widely studied, the reversible voltage is 1.23V, but the current high overpotential of the oxygen reduction reaction results in the actual discharge potential of the hydrogen-oxygen fuel cell being only 0.6-0.8V, and the corresponding voltage efficiency being only 49%-65%, which results in a low energy conversion efficiency. Correspondingly, the almost no overpotential characteristic of chlorine reduction enables hydrogen-chlorine fuel cells to obtain a higher actual discharge potential and voltage efficiency, and therefore is very likely to obtain a high energy conversion efficiency.

[0162] The electrocatalytic chlorine reduction tests were carried out using commercially available carbon nanotube-loaded Pt clusters, RuO2 electrodes and commercial ruthenium-iridium DSA electrodes, respectively. The test conditions were: room temperature and pressure, a three-electrode system H-type electrode cell, the electrolyte was a Cl2-saturated 1M HCl aqueous solution, the working electrode was a carbon nanotube-loaded Pt cluster, RuO2 electrode or commercial ruthenium-iridium DSA electrode, the reference electrode was a saturated calomel electrode, the counter electrode was a graphite rod, and the ion exchange membrane was a Nafion117 membrane. Fig.18 a is the polarization curves of electrocatalytic chlorine reduction of carbon nanotube-supported Pt clusters, RuO2 electrode and commercial ruthenium-iridium DSA electrode.

[0163] Commercially available carbon-supported platinum, carbon-supported iridium, and carbon-supported ruthenium were used for electrocatalytic hydrogen oxidation tests, and the source manufacturer was Sigma-Aldrich. The test conditions were: normal temperature and pressure, rotating disk electrode, electrolyte was H2-saturated 0.1M HClO4 aqueous solution, working electrode was carbon-supported platinum, carbon-supported iridium, or carbon-supported ruthenium, reference electrode was saturated calomel electrode, and counter electrode was graphite rod. Fig.18 b is the polarization curve of electrocatalytic hydrogen oxidation of carbon-supported platinum, carbon-supported iridium and carbon-supported ruthenium.

[0164] Fig.18 a shows that chlorine reduction has almost no overpotential and has good reversibility with the corresponding oxidation chlorine evolution reaction. Among the three electrodes, the Pt clusters supported by carbon nanotubes show the best chlorine reduction performance. Fig.18b shows that hydrogen oxidation has almost no overpotential and has good reversibility with the corresponding reduction hydrogen evolution reaction. Among the three electrodes, carbon-supported iridium shows the best hydrogen oxidation performance.

[0165] Fig.18 In a and b, the preferred carbon nanotube-loaded Pt clusters and carbon-loaded platinum can be used as cathode materials for electrolytic chlorine evolution and hydrogen evolution systems, and anode materials for hydrogen-chlorine fuel cell systems, respectively, in energy cycle systems based on hydrochloric acid electrolysis.

[0166] Small test experiment

[0167] (1) Preparation of electrolyte: dilute concentrated hydrochloric acid with deionized water to obtain a certain volume of 0.1-10 mol L -1 Concentration of dilute hydrochloric acid (10 L in this example, 1 mol L -1 ), and placed in a hydrochloric acid storage device (1).

[0168] (2) Assembly of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system (2): A self-made titanium-based metal oxide electrode is used as the anode (specifically, the Zr obtained in the following example (2) in this example) 0.6 Sb 0.1 Ru 0.3 O2 electrode), the noble metal catalyst is the cathode (in this embodiment, the Pt cluster supported by carbon nanotubes), and the catalyst loading is 2-10 mg cm -2 (In this example, 5 mg cm -2 ), the effective active area of ​​the cathode and anode is 25cm 2 , assembled with other components into membrane electrode, and equipped with temperature and pressure detection devices to monitor the temperature and pressure of the system in real time.

[0169] (3) Using a corrosion-resistant chemical professional liquid pump, the dilute hydrochloric acid of a certain concentration prepared in step (1) is transported into the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system (2) (in this embodiment, 1 mol L -1 , speed 100L / h).

[0170] (4) Intermittent renewable electric energy is connected to the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system (2) assembled in step (2), and the operating conditions are normal temperature and pressure, and the electrolysis is carried out at an electrolysis rate of 50 to 750 mA (250 mA in the present embodiment) in a constant current electrolysis mode, and the corresponding voltage is (1.36 to 1.52 V) (1.41 V in the present embodiment). The generated chlorine and hydrogen pass through a gas-liquid separation device, a condenser tube for dehydration, 3 to 10 concentrated sulfuric acid washing bottles for dehydration (5 in the present embodiment), and then lead to a chlorine and hydrogen collecting device. The rate at which the anode and cathode produce hydrogen and chlorine is about 30 to 110 mL / min (70 mL / min in the present embodiment).

[0171] (5) The chlorine and hydrogen collected in step (4) above are pressurized to 1.8-2.2 MPa by a gas compression and pressurizing device and then passed to a chlorine and hydrogen storage device (2.0 MPa in this embodiment). The gas pressure of the storage device is 1.2-1.5 MPa (1.5 MPa in this embodiment).

[0172] (6) Hydrogen-chlorine fuel cell (7) Assembly: Commercially available carbon-supported platinum was used as the catalyst for chlorine reduction at the cathode and hydrogen oxidation at the anode (sourced from Sigma-Aldrich), with a catalyst loading of 2-10 mg cm -2 (This example is 5 mg cm -2 ), the effective active area of ​​the cathode and anode is 25cm 2 , assembled with other components into a membrane electrode assembly, and equipped with a temperature and pressure detection device to monitor the temperature and pressure of the system in real time.

[0173] (7) When the hydrogen-chlorine fuel cell (7) needs to discharge, the chlorine and hydrogen storage tanks in step (5) are used as fuel, and are controlled by a corrosion-resistant chemical-specific gas flow meter, and are respectively passed to five washing bottles filled with deionized water at a rate of 30 to 110 mL / min to fully contact and wet the water (70 mL / min in this embodiment), and then passed to the hydrogen-chlorine fuel cell for discharge, with a current of 50 to 750 mA (250 mA in this embodiment), a discharge voltage of 1.36 to 1.30 (1.33 V in this embodiment), and a corresponding power of 332.5 mW.

[0174] (8) The hydrogen chloride produced at the cathode in the above step (7) is passed to the hydrogen chloride separation device (8), where the hydrogen chloride is absorbed by washing bottles with 3 to 10 saturated salt water bottles (5 bottles in this embodiment), and the remaining chlorine is circulated back to the chlorine storage device (6).

[0175] (9) The saturated brine in which the hydrogen chloride is dissolved in step (8) is passed to a hydrochloric acid recovery and purification device (9) to purify the hydrogen chloride by distillation at a heating evaporation temperature of 80 to 85° C. (85° C. in this embodiment).

[0176] (10) The purified hydrogen chloride in step (9) is circulated back to the hydrochloric acid storage device (1) in step (1) through the hydrogen chloride reflux pipeline 115, thereby realizing the circulation of materials and energy. The remaining saturated brine is circulated back to the hydrogen chloride gas separation device (8) through the saturated brine reflux pipeline (114).

[0177] Example 1

[0178] Preparation of low-noble metal mixed oxide electrodes for electrocatalytic chloride ion oxidation.

[0179] This embodiment provides Zr x Sb yRu 1-x-y The preparation method of the O2 electrode includes the following steps, and those skilled in the art may make adjustments with reference to the prior art:

[0180] (1) Prepare alcohol solutions of the metals respectively.

[0181] (2) The alcohol solutions prepared in step (1) are mixed in different molar ratios to obtain a uniformly dispersed solution; a high molecular weight polymer having a multidentate ligand is then added to the solution, and the mixture is heated and stirred to allow the solution to react fully.

[0182] (3) The solution obtained in step (2) is evenly brushed onto the porous conductive substrate, and heated and dried. In this embodiment, the porous conductive substrate is titanium felt. The coating-heating and drying process is performed 3 times in total;

[0183] (4) The porous conductive substrate is then placed in a muffle furnace for calcination, fully exposed to air and reacted, and cooled to room temperature in air. The calcination-cooling process is performed 3 times in total;

[0184] (5) The porous conductive substrate is then placed in a muffle furnace for calcination, fully contacted with air, reacted, and tightly combined with the porous conductive substrate and the catalyst on the surface, and then cooled to room temperature in the furnace to obtain Zr x Sb y Ru 1-x-y O2 electrode. In this embodiment, Zr 0.6 Sb 0.1 Ru 0.3 O2 electrode.

[0185] The alcohol solution of the metal in step (1) is an alcohol solution of ruthenium trichloride, zirconium butoxide, or antimony trichloride, and the concentration of each of the solutions is 0.5 mol L -1 ~1mol L -1 , in this example, 0.5 mol L -1 .

[0186] The mixed solution described in step (2) is an alcohol solution of ruthenium trichloride, zirconium butoxide and antimony trichloride; the total metal amount of the mixed solution is 0.5-2mmol, and in this embodiment it is 2mmol, and the molar ratio of ruthenium, zirconium and antimony in the mixed solution is: 3:6:1. The amount of the polymer with multidentate ligand added is 60-240mg, and in this embodiment 240mg of polyvinyl alcohol is added. The temperature of the heating and stirring is 50-90℃, the time is 2-8h, and in this embodiment, it is stirred at 50℃ for 8h.

[0187] The drying temperature in step (3) is 50-90° C., and in this embodiment, it is 90° C. The drying time is 1-20 minutes, and in this embodiment, it is 1 minute.

[0188] The muffle furnace calcination temperature in step (4) is 400-600° C., 600° C. in this embodiment, and the calcination time is 1-20 min, 1 min in this embodiment.

[0189] The temperature of the muffle furnace in step (5) is 400-600°C, and in this embodiment it is 600°C. The calcination time is 0.5-3h, and in this embodiment it is 0.5h. The loading amount of the mixed metal oxide on the surface of the conductive substrate is 1-20mg / cm -2 , the loading thickness is 1-100 μm. The loading amount in this embodiment is 1 mg / cm -2 , the loading thickness is 1 μm.

[0190] The electrode Zr obtained above 0.6 Sb 0.1 Ru 0.3 O2 can be used directly as a working electrode without further treatment.

[0191] Comparative Example 1

[0192] The preparation method of reference example 1 is different from that of example 1 in that the molar ratio of metal ruthenium, zirconium and antimony in the mixed solution is 2:7:1. The prepared electrode is Zr 0.7 Sb 0.1 Ru 0.2 O2.

[0193] Example 2

[0194] The preparation method of reference embodiment 1 is different from that of embodiment 1 only in that the molar ratio of metal zirconium, antimony and ruthenium in the mixed solution is 1:1:8, and the porous conductive substrate is a titanium mesh.

[0195] The prepared electrode is Zr 0.1 Sb 0.1 Ru 0.8 O2.

[0196] Comparative Example 2

[0197] The preparation method of reference embodiment 2 is different from that of embodiment 2 only in that the molar ratio of metal zirconium, antimony and ruthenium in the mixed solution is 5:5:90. The prepared electrode is Zr 0.05 Sb 0.05 Ru 0.9 O2.

[0198] Example 3

[0199] This embodiment provides Zr x V y Ru 1-x-y The preparation method of the O2 electrode includes the following steps, referring to the preparation method of Example 1.

[0200] The alcohol solution of the metal in step (1) is an alcohol solution of ruthenium trichloride, zirconium butoxide, and vanadium trichloride, with a concentration of 0.5 mol L -1 ~1mol L -1 , in this example, 0.5 mol L -1 .

[0201] The mixed solution described in step (2) is an alcohol solution of ruthenium trichloride, zirconium butoxide, and vanadium trichloride; the total metal amount of the mixed solution is 0.5-2mmol, and in this embodiment it is 2mmol, and the molar ratio of ruthenium, zirconium, and vanadium in the mixed solution is: 3:6:1. The amount of the polymer with multidentate ligand added is 60-240mg, and in this embodiment 240mg of polyethylene glycol is added. The temperature of the heating and stirring is 50-90℃, the time is 2-8h, and in this embodiment it is stirred at 80℃ for 4h. And the porous conductive substrate is carbon paper.

[0202] The drying temperature in step (3) is 50-90° C., and in this embodiment, it is 80° C. The drying time is 1-20 minutes, and in this embodiment, it is 5 minutes.

[0203] The muffle furnace calcination temperature in step (4) is 400-600° C., 500° C. in this embodiment, and the calcination time is 1-20 min, 5 min in this embodiment.

[0204] The temperature of the muffle furnace in step (5) is 400-600°C, and in this embodiment it is 500°C. The calcination time is 0.5-3h, and in this embodiment it is 1h. The loading amount of the mixed metal oxide on the surface of the conductive substrate is 1-20mg / cm -2 , the loading thickness is 1-100 μm. The loading amount in this embodiment is 4.2 mg / cm -2 , the loading thickness is 37μm.

[0205] The electrode Zr obtained above 0.6 V 0.1 Ru 0.3 O2 can be used directly as a working electrode without further treatment.

[0206] Comparative Example 3

[0207] The preparation method of reference embodiment 3 is different from that of embodiment 3 only in that the molar ratio of metal zirconium, vanadium and ruthenium in the mixed solution is 7:1:2. The prepared electrode is Zr 0.7 V 0.1 Ru 0.2 O2.

[0208] Example 4

[0209] The preparation method of reference embodiment 3 is different from that of embodiment 3 only in that the molar ratios of metal zirconium, vanadium and ruthenium in the mixed solution are 1:1:8 respectively, and the porous conductive substrate is carbon cloth.

[0210] The prepared electrode is Zr 0.1 V 0.1 Ru 0.8 O2.

[0211] Comparative Example 4

[0212] The preparation method of reference embodiment 4 is different from that of embodiment 4 only in that the molar ratio of metal zirconium, vanadium and ruthenium in the mixed solution is 5:5:90. The prepared electrode is Zr 0.05 V 0.05 Ru 0.9 O2.

[0213] Example 5

[0214] Preparation of low-noble metal mixed oxide electrodes for electrocatalytic chloride ion oxidation.

[0215] This embodiment provides Sn x Nb y Ru 1-x-y The preparation method of the O2 electrode includes the following steps, referring to the preparation method of Example 1.

[0216] The metal alcohol solution in step (1) is an alcohol solution of ruthenium trichloride, tin tetrachloride, and niobium pentachloride, and the concentration is 0.5 mol L -1 ~1mol L -1 , in this example, 0.5 mol L -1 .

[0217] The mixed solution described in step (2) is an alcohol solution of ruthenium trichloride, tin tetrachloride and niobium pentachloride; the total metal amount of the mixed solution is 2 mmol, and the molar ratio of ruthenium, tin and niobium in the mixed solution is 3:6:1. The amount of the polymer with multidentate ligand added is 60-240 mg, and in this embodiment, 240 mg of polyethylenediamine is added. The temperature of the heating and stirring is 50-90°C, the time is 2-8h, and in this embodiment, the stirring is 6h at 60°C.

[0218] The drying temperature in step (3) is 50-90° C., and in this embodiment, it is 60° C. The drying time is 1-20 minutes, and in this embodiment, it is 10 minutes.

[0219] The muffle furnace calcination temperature in step (4) is 400-600° C., 450° C. in this embodiment, and the calcination time is 1-20 min, 10 min in this embodiment.

[0220] The temperature of the muffle furnace in step (5) is 400-600°C, and in this embodiment it is 450°C. The calcination time is 0.5-3h, and in this embodiment it is 2h. The loading amount of the mixed metal oxide on the surface of the conductive substrate is 1-20mg / cm -2 , the loading thickness is 1-100 μm. The loading amount in this embodiment is 3.8 mg / cm -2 , the loading thickness is 35μm.

[0221] The Sn electrode obtained above 0.6 Nb 0.1 Ru 0.3 O2 can be used directly as a working electrode without further treatment.

[0222] Comparative Example 5

[0223] The preparation method of reference embodiment 5 is different from that of embodiment 5 only in that the molar ratio of metal tin, niobium and ruthenium in the mixed solution is 7:1:2. The prepared electrode is Sn 0.7 Nb 0.1 Ru 0.2 O2.

[0224] Example 6

[0225] The preparation method of reference embodiment 5 is different from that of embodiment 5 only in that the molar ratio of metal tin, niobium and ruthenium in the mixed solution is 1:1:8. The prepared electrode is Sn 0.1 Nb 0.1 Ru 0.8 O2.

[0226] Comparative Example 6

[0227] The preparation method of reference embodiment 5 is different from that of embodiment 5 only in that the molar ratio of metal tin, niobium and ruthenium in the mixed solution is 5:5:90. The prepared electrode is Sn 0.05 Nb 0.05 Ru 0.9 O2.

[0228] Example 7

[0229] Preparation of low-noble metal mixed oxide electrodes for electrocatalytic chloride ion oxidation.

[0230] This embodiment provides Sn x Ti y Ru 1-x-y The preparation method of the O2 electrode includes the following steps, referring to the preparation method of Example 1.

[0231] The alcohol solution of the metal in step (1) is an alcohol solution of ruthenium trichloride, tin tetrachloride, and tetrabutyl titanate, with a concentration of 0.5 mol L -1~1mol L -1 , all in this example are 1 mol L -1 .

[0232] The mixed solution described in step (2) is an alcohol solution of ruthenium trichloride, tin tetrachloride and tetrabutyl titanate; the total metal amount of the mixed solution is 0.5 mmol, and the molar ratio of ruthenium, tin and titanium in the mixed solution is 3:6:1. The amount of the polymer with multidentate ligand added is 60-240 mg, and in this embodiment, 60 mg of polyvinyl pyrrolidone is added. The temperature of the heating and stirring is 50-90°C, the time is 2-8h, and in this embodiment, the stirring is 90°C for 2h.

[0233] The drying temperature in step (3) is 50-90° C., and in this embodiment it is 50° C. The drying time is 1-20 min, and in this embodiment it is 20 min.

[0234] The muffle furnace calcination temperature in step (4) is 400-600° C., 400° C. in this embodiment, and the calcination time is 1-20 min, 20 min in this embodiment.

[0235] The temperature of the muffle furnace in step (5) is 400-600°C, and in this embodiment it is 400°C. The calcination time is 0.5-3h, and in this embodiment it is 3h. The loading amount of the mixed metal oxide on the surface of the conductive substrate is 1-20mg / cm -2 , the loading thickness is 1-100 μm. The loading amount in this embodiment is 20 mg / cm -2 , the loading thickness is 100 μm.

[0236] The Sn electrode obtained above 0.6 Ti 0.1 Ru 0.3 O2 can be used directly as a working electrode without further treatment.

[0237] Comparative Example 7

[0238] The preparation method of reference embodiment 7 is different from that of embodiment 7 only in that the molar ratio of metal tin, titanium and ruthenium in the mixed solution is 7:1:2. The prepared electrode is Sn 0.7 Ti 0.1 Ru 0.2 O2.

[0239] Example 8

[0240] The preparation method of reference embodiment 7 is different from that of embodiment 7 only in that the molar ratio of metal tin, titanium and ruthenium in the mixed solution is 1:1:8. The prepared electrode is Sn 0.1 Ti 0.1 Ru 0.8 O2.

[0241] Comparative Example 8

[0242] The preparation method of reference embodiment 8 is different from that of embodiment 8 only in that the molar ratio of metal tin, titanium and ruthenium in the mixed solution is 5:5:90. The prepared electrode is Sn 0.05 Ti 0.05 Ru 0.9 O2.

[0243] Example 9

[0244] Preparation of low-noble metal mixed oxide electrodes for electrocatalytic chloride ion oxidation.

[0245] This embodiment provides Ti x Sn y Sb z Ru 1-x-y-z The preparation method of the O2 electrode includes the following steps, referring to the preparation method of Example 1.

[0246] The alcohol solution of the metal in step (1) is an alcohol solution of tetrabutyl titanate, tin tetrachloride, antimony trichloride, and ruthenium trichloride, with a concentration of 0.5 mol L -1 ~1mol L -1 , all in this example are 1 mol L -1 .

[0247] The mixed solution described in step (2) is an alcohol solution of tetrabutyl titanate, tin tetrachloride, antimony trichloride, and ruthenium trichloride; the total metal amount of the mixed solution is 0.5 mmol, and the molar ratio of ruthenium, titanium, tin, and antimony in the mixed solution is: 3:2:2:3. The amount of the polymer with multidentate ligand added is 60-240 mg, and in this embodiment, 120 mg of polyvinyl pyrrolidone is added. The temperature of the heating and stirring is 50-90°C, the time is 2-8h, and in this embodiment, it is stirred at 80°C for 2h.

[0248] The drying temperature in step (3) is 50-90° C., and in this embodiment, it is 60° C. The drying time is 1-20 minutes, and in this embodiment, it is 10 minutes.

[0249] The muffle furnace calcination temperature in step (4) is 400-600° C., 450° C. in this embodiment, and the calcination time is 1-20 min, 10 min in this embodiment.

[0250] The temperature of the muffle furnace in step (5) is 400-600°C, and in this embodiment it is 450°C. The calcination time is 0.5-3h, and in this embodiment it is 2h. The loading amount of the mixed metal oxide on the surface of the conductive substrate is 1-20mg / cm -2, the loading thickness is 1-100 μm. The loading amount in this embodiment is 15 mg / cm -2 , the loading thickness is 80μm.

[0251] The electrode Ti obtained above 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2 can be used directly as a working electrode without further treatment.

[0252] Example 10

[0253] Preparation of low-noble metal mixed oxide electrodes for electrocatalytic chloride ion oxidation.

[0254] This embodiment provides Nb x Zr y V z Ru 1-x-y-z The preparation method of the O2 electrode includes the following steps, referring to the preparation method of Example 1.

[0255] The alcohol solution of the metal in step (1) is an alcohol solution of niobium pentachloride, zirconium tetrachloride, vanadium trichloride, and ruthenium trichloride, with a concentration of 0.5 mol L -1 ~1mol L -1 , all in this example are 1 mol L -1 .

[0256] The mixed solution described in step (2) is an alcohol solution of niobium pentachloride, zirconium tetrachloride, vanadium trichloride and ruthenium trichloride; the total metal amount of the mixed solution is 0.5 mmol, and the molar ratio of ruthenium, niobium, zirconium and vanadium in the mixed solution is 3:2:2:3. The amount of the polymer with multidentate ligand added is 60-240 mg, and in this embodiment, 150 mg of polyvinyl pyrrolidone is added. The temperature of the heating and stirring is 50-90°C, the time is 2-8h, and in this embodiment, the stirring is 70°C for 5h.

[0257] The drying temperature in step (3) is 50-90° C., and in this embodiment it is 70° C. The drying time is 1-20 min, and in this embodiment it is 10 min.

[0258] The muffle furnace calcination temperature in step (4) is 400-600° C., 450° C. in this embodiment, and the calcination time is 1-20 min, 10 min in this embodiment.

[0259] The temperature of the muffle furnace in step (5) is 400-600°C, and in this embodiment it is 450°C. The calcination time is 0.5-3h, and in this embodiment it is 2h. The loading amount of the mixed metal oxide on the surface of the conductive substrate is 1-20mg / cm -2, the loading thickness is 1-100 μm. The loading amount in this embodiment is 12 mg / cm -2 , the loading thickness is 70μm.

[0260] The electrode Nb obtained above 0.2 Zr 0.2 V 0.3 Ru 0.3 O2 can be used directly as a working electrode without further treatment.

[0261] Embodiment 11

[0262] Preparation of low-noble metal mixed oxide electrodes for electrocatalytic chloride ion oxidation.

[0263] This embodiment provides Co x Fe y Ni z Ru 1-x-y-z The preparation method of the O2 electrode includes the following steps, referring to the preparation method of Example 1.

[0264] The alcohol solution of the metal in step (1) is an alcohol solution of cobalt trichloride, ferric chloride, nickel chloride, and ruthenium trichloride, with a concentration of 0.5 mol L -1 ~1mol L -1 , all in this example are 1 mol L -1 .

[0265] The mixed solution described in step (2) is an alcohol solution of cobalt trichloride, ferric trichloride, vanadium trichloride and nickel chloride; the total metal amount of the mixed solution is 0.5 mmol, and the molar ratio of ruthenium, niobium, zirconium and vanadium in the mixed solution is 7:1:1:1. The amount of the polymer with multidentate ligand added is 60-240 mg, and in this embodiment, 150 mg of polyvinyl pyrrolidone is added. The temperature of the heating and stirring is 50-90°C, the time is 2-8h, and in this embodiment, the stirring is 80°C for 5h.

[0266] The drying temperature in step (3) is 50-90° C., and in this embodiment it is 70° C. The drying time is 1-20 min, and in this embodiment it is 10 min.

[0267] The muffle furnace calcination temperature in step (4) is 400-600° C., 450° C. in this embodiment, and the calcination time is 1-20 min, 10 min in this embodiment.

[0268] The temperature of the muffle furnace in step (5) is 400-600°C, and in this embodiment it is 450°C. The calcination time is 0.5-3h, and in this embodiment it is 2h. x Fe y Ni z Ru1-x-y-z In the O2 electrode, the loading amount of mixed metal oxides on the conductive substrate surface is 1-20 mg / cm -2 , the loading thickness is 1-100 μm. The loading amount in this embodiment is 12 mg / cm -2 , the loading thickness is 70μm.

[0269] The electrode Co obtained above 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2 can be used directly as a working electrode without further treatment.

[0270] Example 12

[0271] Preparation of low-noble metal mixed oxide electrodes for electrocatalytic chloride ion oxidation.

[0272] This embodiment provides Ti a Sn b Sb c Nb d Zr e V f Co g Fe h Ni i Ru j The preparation method of the O2 electrode includes the following steps, referring to the preparation method of Example 1.

[0273] The alcohol solution of the metal in step (1) is an alcohol solution of tetrabutyl titanate, tin tetrachloride, antimony trichloride, niobium pentachloride, zirconium tetrachloride, vanadium trichloride, cobalt trichloride, iron trichloride, nickel chloride, and ruthenium trichloride, with a concentration of 0.5 mol L -1 ~1molL -1 , all in this example are 1 mol L -1 .

[0274] The mixed solution described in step (2) is an alcohol solution of tetrabutyl titanate, tin tetrachloride, antimony trichloride, niobium pentachloride, zirconium tetrachloride, vanadium trichloride, cobalt trichloride, ferric chloride, nickel chloride, and ruthenium trichloride; the total metal amount of the mixed solution is 0.5mmol, and the molar ratio of titanium, tin, antimony, niobium, zirconium, vanadium, cobalt, iron, nickel, and ruthenium in the mixed solution is 14:7:7:7:7:7:7:7:7:30. The amount of the high molecular polymer with multidentate ligand added is 60-240mg, and in this embodiment, 150mg of polyvinyl pyrrolidone is added. The temperature of the heating and stirring is 50-90℃, the time is 2-8h, and in this embodiment, it is stirred at 80℃ for 4h.

[0275] The drying temperature in step (3) is 50-90° C., and in this embodiment it is 70° C. The drying time is 1-20 min, and in this embodiment it is 10 min.

[0276] The muffle furnace calcination temperature in step (4) is 400-600° C., 450° C. in this embodiment, and the calcination time is 1-20 min, 10 min in this embodiment.

[0277] The temperature of the muffle furnace in step (5) is 400-600°C, and in this embodiment it is 450°C. The calcination time is 0.5-3h, and in this embodiment it is 2h. The loading amount of the mixed metal oxide on the surface of the conductive substrate is 1-20mg / cm -2 , the loading thickness is 1-100 μm. The loading amount in this embodiment is 10 mg / cm -2 , the loading thickness is 60μm.

[0278] The electrode Ti obtained above 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.07 Ni 0.07 Ru 0.3 O2 can be used directly as a working electrode without further treatment.

[0279] Morphological characterization:

[0280] The morphology of the low-noble metal mixed oxide electrode obtained above was characterized.

[0281] The electrodes obtained in Examples 1, 3, 5 and 7 were subjected to scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) tests. Figure 1 a, b, c, d are Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 From the SEM images of the O2 electrodes, it can be seen that the surfaces of the four electrodes are all uniformly mud-cracked, which is the typical morphology of sintered oxide electrodes. Figure 2 , 3 , 4, 5 respectively Zr 0.6 Sb 0.1 Ru 0.3O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 The surface element distribution diagram of the O2 electrode shows that the metal elements in the prepared mixed metal oxide are evenly dispersed.

[0282] Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 The O2 electrode was ultrasonicated and centrifugally dried in an alcohol solution to obtain its surface particles, and the surface particles were tested by transmission electron microscopy (TEM). The results are as follows Figure 6 As shown, a, b, c, and d are Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 The TEM image corresponding to the O2 electrode shows that the surface of the prepared mixed metal oxide electrode is composed of nanoparticles with a size of 5 to 100 nanometers.

[0283] Application Example 1

[0284] Electrochemical performance and chlorine selectivity test of low-noble metal mixed oxide electrodes used for electrocatalytic chloride ion oxidation in hydrochloric acid.

[0285] The performance and selectivity of the electrodes obtained in Examples 1, 3, 5, 7, 9, 10, 11, and 12 for electrocatalytic production of chlorine under acidic conditions were tested.

[0286] The test method is as follows:

[0287] At room temperature, a two-chamber H-type electrolytic cell with a diaphragm was connected to an electrochemical workstation for testing. The diaphragm was Nation 117 proton exchange membrane, the single-chamber capacity of the electrolytic cell was 50 mL, the Ag / AgCl electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the prepared electrode and the commercial ruthenium-iridium DSA electrode were working electrodes, and 40 mL of 1 mol L was added to each side of the electrolytic cell. -1 The hydrochloric acid solution (pH=0) was used as the electrolyte. The performance test of electrocatalytic chlorine production was carried out using a linear sweep voltammetric test system. The chlorine content obtained by electrolyzing the hydrochloric acid solution was measured using the iodine titration method and compared with the theoretical value to obtain the selectivity of chlorine.

[0288] Figure 7 The nine curves A, B, C, D, E, F, G, H, and I are Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2、Ti 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.07 Ni 0.07 Ru 0.3 Polarization curves of O2 electrode and commercial ruthenium iridium DSA electrode. It can be seen that the overpotentials at a current density of 10 mA / cm2 are 43 mV, 50 mV, 45 mV, 53 mV, 51 mV, 48 mV, 55 mV and 56 mV, respectively, which are all lower than 60 mV of the commercial ruthenium iridium DSA electrode, indicating that the electrodes obtained in Examples 1, 3, 5, 7, 9, 10, 11 and 12 have better electrochemical activity than the commercial ruthenium iridium DSA electrode.

[0289] Figure 8 A, B, C, D, E, F, G, H, and I are Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2、Ti 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.07 Ni 0.07 Ru 0.3 Chlorine selectivity bar graph of O2 electrode and commercial Ruthenium-Iridium DSA electrode, where Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2、Ti 0.14 Sn 0.07 Sb0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.07 Ni 0.07 Ru 0.3 The selectivity of the O2 electrode for producing chlorine was 94.0%, 93.3%, 92.4%, 93.7%, 93.6%, 90.6%, 89.3% and 88.7%, respectively, all of which were higher than 87.4% of the commercial ruthenium-iridium DSA electrode, indicating that the electrodes obtained in Examples 1, 3, 5, 7, 9, 10, 11 and 12 all had higher chlorine selectivity than the commercial ruthenium-iridium DSA electrode.

[0290] The above tests fully demonstrate that the low-noble metal mixed oxide electrode obtained by the sol-gel method has better electrochemical performance and higher chlorine selectivity than the commercial ruthenium-iridium DSA electrode.

[0291] Application Example 2

[0292] The performance of electrocatalytic chlorine production was tested on the electrodes obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2, and the commercial ruthenium-iridium DSA electrode. The testing method was the same as that in Application Example 1.

[0293] The obtained polarization curve is Fig. 9 As shown, curves A, B, C, D, and E are respectively the Zr 0.6 Sb 0.1 Ru 0.3 O2 electrode, Zr obtained in Example 2 0.1 Sb 0.1 Ru 0.8 O2 electrode, Zr obtained in Comparative Example 1 0.7 Sb 0.1 Ru 0.2 O2 electrode, Zr obtained in Comparative Example 2 0.05 Sb 0.05 Ru 0.9 Polarization curves of O2 electrode and commercial Ru-Ir DSA electrode.

[0294] It can be seen that the performance of the electrodes obtained in Examples 1 and 2 in electrocatalytically producing chlorine is better than that of the commercial ruthenium-iridium DSA electrode.

[0295] The performance of the electrodes obtained in Comparative Examples 1 and 2 in electrocatalytic production of chlorine is significantly worse than that of the electrodes obtained in Examples 1 and 2 and the commercial ruthenium-iridium DSA electrode. The overpotentials at a current density of 10 mA per square centimeter are 84 mV and 65 mV, respectively, which are much greater than the electrodes obtained in Examples 1 and 2 (overpotentials of 43 mV and 52 mV) and the commercial ruthenium-iridium DSA electrode (overpotential of 60 mV).

[0296] Application Example 3

[0297] The performance of electrocatalytic chlorine production was tested on the electrodes obtained in Example 3, Example 4, Comparative Example 3 and Comparative Example 4, and the commercial ruthenium-iridium DSA electrode. The testing method was the same as that in Application Example 1.

[0298] The obtained polarization curve is Fig.10 As shown, curves A, B, C, D, and E are respectively the Zr 0.6 Sb 0.1 Ru 0.3 O2 electrode, Zr obtained in Example 4 0.1 V 0.1 Ru 0.8 O2 electrode, Zr obtained in Comparative Example 3 0.7 V 0.1 Ru 0.2 O2 electrode, Zr obtained in Comparative Example 4 0.05 V 0.05 Ru 0.9 Polarization curves of O2 electrode and commercial Ru-Ir DSA electrode.

[0299] It can be seen that the performance of the electrodes obtained in Examples 3 and 4 in electrocatalytically producing chlorine is better than that of the commercial ruthenium-iridium DSA electrode.

[0300] The performance of the electrodes obtained in Comparative Examples 3 and 4 in electrocatalytic production of chlorine is significantly worse than that of the electrodes obtained in Examples 3 and 4 and the commercial ruthenium-iridium DSA electrode. The overpotentials at a current density of 10 mA per square centimeter are 108 mV and 76 mV, respectively, which are much greater than the electrodes obtained in Examples 3 and 4 (overpotentials of 50 mV and 49 mV) and the commercial ruthenium-iridium DSA electrode (overpotential of 60 mV).

[0301] Application Example 4

[0302] The performance of electrocatalytic chlorine production was tested on the electrodes obtained in Example 5, Example 6, Comparative Example 5 and Comparative Example 6 and the commercial ruthenium-iridium DSA electrode. The testing method was the same as that in Application Example 1.

[0303] The obtained polarization curve is Fig.11 As shown, curves A, B, C, D, and E are respectively Sn obtained in Example 5. 0.6 Nb 0.1 Ru 0.3 O2 electrode, Sn obtained in Example 6 0.1 Nb 0.1 Ru 0.8 O2 electrode, Sn obtained in Comparative Example 5 0.7 Nb 0.1 Ru 0.2 O2 electrode, Sn obtained in Comparative Example 60.05 Nb 0.05 Ru 0.9 Polarization curves of O2 electrode and commercial Ru-Ir DSA electrode.

[0304] It can be seen that the performance of the electrodes obtained in Examples 5 and 6 in electrocatalytically producing chlorine is better than that of the commercial ruthenium-iridium DSA electrode.

[0305] The performance of the electrodes obtained in Comparative Examples 5 and 6 in electrocatalytic production of chlorine is significantly worse than that of the electrodes obtained in Examples 5 and 6 and the commercial ruthenium-iridium DSA electrode. The overpotentials at a current density of 10 mA per square centimeter are 90 mV and 63 mV, respectively, which are much greater than the electrodes obtained in Examples 5 and 6 (45 mV, 48 mV) and the commercial ruthenium-iridium DSA electrode (60 mV).

[0306] Application Example 5

[0307] The performance of electrocatalytic chlorine production was tested on the electrodes obtained in Example 7, Example 8, Comparative Example 7 and Comparative Example 8 and the commercial ruthenium-iridium DSA electrode. The testing method was the same as that in Application Example 1.

[0308] The obtained polarization curve is Fig.12 As shown, curves A, B, C, D, and E are respectively Sn obtained in Example 7. 0.6 Ti 0.1 Ru 0.3 O2 electrode, Sn obtained in Example 8 0.1 Ti 0.1 Ru 0.8 O2 electrode, Sn obtained in Comparative Example 7 0.7 Ti 0.1 Ru 0.2 O2 electrode, Sn obtained in Comparative Example 8 0.05 Ti 0.05 Ru 0.9 Polarization curves of O2 electrode and commercial Ru-Ir DSA electrode.

[0309] It can be seen that the performance of the electrodes obtained in Examples 7 and 8 in electrocatalytically producing chlorine is better than that of the commercial ruthenium-iridium DSA electrode.

[0310] The performance of the electrodes obtained in Comparative Examples 7 and 8 in electrocatalytic production of chlorine is significantly worse than that of the electrodes obtained in Examples 7 and 8 and the commercial ruthenium-iridium DSA electrode. The overpotentials at a current density of 10 mA per square centimeter are 106 mV and 67 mV, respectively, which are much larger than the electrodes obtained in Examples 7 and 8 (53 mV, 54 mV) and the commercial ruthenium-iridium DSA electrode (60 mV).

[0311] It can be seen from Application Examples 2-5 that too much or too little element doping cannot achieve the ideal effect: when the element doping is small (i.e., x<20%), the performance of the ruthenium dioxide electrode does not change significantly, and its preparation cost does not decrease significantly, and its actual application value is not great; when the element doping is large (i.e., x>70%), due to the excessive proportion of doped metal, the original crystal structure of ruthenium dioxide is greatly distorted, resulting in changes in the electrode structure, and the electrode performance drops sharply, which is lower than the commercial ruthenium-iridium DSA electrode.

[0312] Application Example 6

[0313] Electrochemical stability testing of low-noble metal mixed oxide electrodes used for electrocatalytic chloride ion oxidation.

[0314] The electrodes obtained in Examples 1, 3, 5 and 7 were tested for their stability in electrocatalytic production of chlorine.

[0315] The test method is as follows:

[0316] At room temperature, a two-chamber H-type electrolytic cell with a diaphragm was connected to an electrochemical workstation for testing. The diaphragm was Nation 117 proton exchange membrane, the single-chamber capacity of the electrolytic cell was 50 mL, the Ag / AgCl electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the prepared electrode and the commercial ruthenium-iridium DSA electrode were working electrodes, and 40 mL of 1 mol L was added to each side of the electrolytic cell. -1 The hydrochloric acid solution was used as the electrolyte and replenished regularly. The stability test of electrocatalytic chlorine production was carried out using a constant current test system.

[0317] Fig.13 A, B, C, D, and E are Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 From the stability test results of the electrocatalytic chlorine production of the O2 electrode and the commercial ruthenium-iridium DSA electrode, it can be seen that the voltages required for the electrodes obtained in Examples 1, 3, 5, and 7 to achieve the same current density (100 milliamperes per square centimeter) are 1.44, 1.45, 1.45, and 1.47 (volts, relative to a standard hydrogen electrode), respectively, which are lower than those of the commercial ruthenium-iridium DSA electrode (1.49 volts, relative to a standard hydrogen electrode). They can all work stably for 500 hours at a current density of 100 milliamperes per square centimeter without a significant increase in voltage.

[0318] This indicates that the low-noble metal mixed oxide electrode obtained by the sol-gel method has excellent electrochemical stability comparable to that of the commercial ruthenium-iridium DSA electrode.

[0319] Application Example 7

[0320] Electrochemical performance test of low-noble metal mixed oxide electrode used for electrocatalytic chloride ion oxidation in neutral salt water.

[0321] The performance of the electrodes obtained in Examples 1, 3, 5, 7, 9, 10, 11, and 12 and the commercial ruthenium-iridium DSA electrode in electrocatalytic production of hypochlorous acid under neutral conditions was tested.

[0322] Refer to the test method of Application Example 1. The only difference from Application Example 1 is that the electrolyte is 1 mol L -1 Sodium chloride solution (pH=7) was used as the electrolyte.

[0323] Fig.14 A, B, C, D, E, F, G, H, and I are Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2、Ti 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.07 Ni 0.07 Ru 0.3 The polarization curves of the O2 electrode and the commercial Ru-Ir DSA electrode for electrocatalytic production of hypochlorous acid in neutral electrolyte show that Zr 0.6 Sb 0.1 Ru 0.3O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2、Ti 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.07 Ni 0.0 7Ru 0.3 The peak potential and current growth rate of the O2 electrode are better than those of the commercial ruthenium-iridium DSA electrode.

[0324] Application Example 8

[0325] Electrochemical performance test of low-noble metal mixed oxide electrode used for electrocatalytic chloride ion oxidation in alkaline salt water.

[0326] The performance of the electrodes obtained in Examples 1, 3, 5, 7, 9, 10, 11, and 12 and the commercial ruthenium-iridium DSA electrode in electrocatalytic production of hypochlorite under alkaline conditions was tested.

[0327] Refer to the test method of Application Example 1. The only difference from Application Example 1 is that the electrolyte is 1 mol L -1 A potassium chloride solution (adjusted to pH = 10 with potassium hydroxide) was used as the electrolyte.

[0328] Fig.15 A, B, C, D, E, F, G, H, and I are Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2、Ti 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.07 Ni 0.07 Ru 0.3 The polarization curves of the electrocatalytic production of hypochlorite by O2 electrode and commercial ruthenium-iridium DSA electrode in alkaline electrolyte show that Zr 0.6 Sb 0.1 Ru 0.3 O2、Zr 0.6 V 0.1 Ru 0.3 O2、Sn 0.6 Nb 0.1 Ru 0.3 O2、Sn 0.6 Ti 0.1 Ru 0.3 O2、Ti 0.2 Sn 0.2 Sb 0.3 Ru 0.3 O2、Nb 0.2 Zr 0.2 V 0.3 Ru 0.3 O2、Co 0.1 Fe 0.1 Ni 0.1 Ru 0.7 O2、Ti 0.14 Sn 0.07 Sb 0.07 Nb 0.07 Zr 0.07 V 0.07 Co 0.07 Fe 0.07 Ni 0.0 7Ru 0.3 The peak potential and current growth rate of the O2 electrode are better than those of the commercial ruthenium-iridium DSA electrode.

[0329] It can be seen from Application Examples 1, 7 and 8 that the low-noble metal mixed oxide electrode obtained by the sol-gel method has better electrochemical performance than the commercial ruthenium-iridium DSA electrode in chloride ion solutions under different pH conditions (0-10).

Claims

1. An energy circulation system based on hydrochloric acid electrolysis, characterized in that: The energy circulation system comprises: a hydrochloric acid storage device (1), a hydrochloric acid electrolysis hydrogen and chlorine evolution system (2), a hydrogen storage device (5), a chlorine storage device (6), and a hydrogen-chlorine fuel cell (7); The hydrochloric acid storage device (1) is connected to the anode of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system (2) through a material hydrochloric acid input pipeline (101), or the hydrochloric acid storage device (1) is respectively connected to the anode and cathode of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system (2) through a material hydrochloric acid input pipeline (101), the anode of the electrolytic hydrochloric acid hydrogen evolution and chlorine evolution system (2) is connected to the chlorine storage device (6), and the chlorine storage device (6) is connected to the cathode of the hydrogen-chlorine fuel cell (7) through a chlorine input pipeline (109); The cathode of the hydrochloric acid electrolysis hydrogen and chlorine evolution system (2) is connected to a hydrogen storage device (5), and the hydrogen storage device (5) is connected to an anode of the hydrogen-chlorine fuel cell (7) via a hydrogen input pipeline (108); The cathode of the hydrogen-chlorine fuel cell (7) is also connected to the hydrochloric acid storage device (1).

2. The energy circulation system based on hydrochloric acid electrolysis according to claim 1 is characterized in that: The energy circulation system further comprises a chlorine separation device (4); The anode of the hydrochloric acid electrolysis hydrogen evolution and chlorine evolution system (2) is connected to the chlorine separation device (4) through a chlorine / hydrochloric acid output pipeline (102), and the chlorine separation device (4) is connected to the chlorine storage device (6) through a chlorine output pipeline (105); A chlorine compression device is provided in the chlorine storage device (6), or a chlorine compression device is provided between the chlorine output pipeline (105) and the chlorine storage device (6).

3. The energy circulation system based on hydrochloric acid electrolysis according to claim 2 is characterized in that: The lower part of the chlorine separation device (4) is connected to the hydrochloric acid storage device (1) through a second hydrochloric acid reflux pipeline (107).

4. The energy circulation system based on hydrochloric acid electrolysis according to claim 1 is characterized in that: The energy circulation system further comprises a hydrogen separation device (3); The cathode of the hydrochloric acid electrolysis hydrogen and chlorine evolution system (2) is connected to the hydrogen separation device (3) through a hydrogen / hydrochloric acid output pipeline (103), and the hydrogen separation device (3) is connected to the hydrogen storage device (5) through a hydrogen output pipeline (104); The lower part of the hydrogen separation device (3) is connected to the hydrochloric acid storage device (1) through a first hydrochloric acid reflux pipeline (106).

5. The energy circulation system based on hydrochloric acid electrolysis according to claim 1 is characterized in that: The energy circulation system further comprises a chlorine / hydrogen chloride separation device (8); The cathode of the hydrogen-chlorine fuel cell (7) is connected to the chlorine / hydrogen chloride separation device (8) via a chlorine / hydrogen chloride output pipeline (111), the upper part of the chlorine / hydrogen chloride separation device (8) is connected to the chlorine storage device (6) via a chlorine return pipeline (112), and the lower part of the chlorine / hydrogen chloride separation device (8) is connected to the hydrochloric acid storage device (1).

6. The energy circulation system based on hydrochloric acid electrolysis according to claim 5 is characterized in that: The energy circulation system also includes a hydrochloric acid recovery and purification device (9); The lower part of the chlorine / hydrogen chloride separation device (8) is connected to the hydrochloric acid recovery and purification device (9) through a hydrochloric acid / saturated brine transport pipeline (113); one outlet of the hydrochloric acid recovery and purification device (9) is connected to the hydrochloric acid storage device (1) through a hydrogen chloride reflux pipeline (115); and the other outlet of the hydrochloric acid recovery and purification device (9) is connected to the chlorine / hydrogen chloride separation device (8) through a saturated brine reflux pipeline (114).

7. The energy circulation system based on hydrochloric acid electrolysis according to claim 1 is characterized in that: The anode of the hydrogen-chlorine fuel cell (7) is also connected to the hydrogen storage device (5) via a hydrogen return pipe (110).

Citation Information

Patent Citations

  • A lithium chloride battery and its energy storage method

    CN106785242B